Deciphering preferred solid-state conformations in nitrogen-containing bisphosphonates and their coordination compounds. A case study of discrete Cu(ii) complexes based on Cα-substituted analogues of zoledronic acid: crystal structures and solid-state characterization. Issue 29 (1st July 2019) - Rojek, Tomasz; Goldeman, Waldemar; Ślepokura, Katarzyna; Zierkiewicz, Wiktor; Matczak-Jon, Ewa
Abstract : Conformation diversity of N-containing bisphosphonic acids and related anions within their metal complexes and salts. Abstract : Crystal structures retrieved from the CSD have been used to evaluate conformational preferences of N-containing bisphosphonic acids and related H n L (4− n )− ( n = 0–4) anions within their metal complexes and salts. The search has been performed on 186 crystallographically independent ligand moieties of 11 various N-containing (R)H2 Cα –C(PO3 H2 )2 (OH) bisphosphonic acids and related anions based on the values of the τ 1 (R–Cα –C–O) dihedral angle reflecting the position of a hydroxyl O atom and phosphonate/phosphonic groups with respect to the R side chain. It has been found that most bisphosphonic/bisphosphonate moieties with alkyl and heteroaromatic chains prefer synclinal ( sc ) conformation in the solid state, while antiperiplanar ( ap ) conformation is adopted by less than 10% of ligand moieties. In turn, α, α-disubstituted analogues of zoledronic acid with methyl groups (1 ) or a cyclopropane (2 ), cyclobutane (3 ) or cyclopentane (4 ) ring on the Cα carbon reveal greater conformational diversity. DFT calculations were performed in the gas phase assisted by rationalizing the conformational behaviour of1–4 and related metal-coordinated anions in the structures obtained so far. It has been demonstrated that stable conformations predicted based on calculations basically match experimentally observed ones, and the same observation pertains to the newly synthesized five-coordinate Cu(H3 dmtZol)2 (H2 O)·8H2 O (1a ) and six-coordinate trans -Cu(H3 cbtZol)2 (H2 O)2 (3a ) and trans -Cu(H3 cptZol)2 (H2 O)2 (4a ) complexes. Single-crystal X-ray diffraction studies have revealed that all1a, 3a and4a coordinated ligands adopt sc conformation. Compound1a exhibits an almost ideal square pyramidal geometry around Cu(ii ). A striking finding for3a and4a is great tetragonal elongation with coaxial Cu–O1W bonds approaching 2.733(3) and 2.725(3) Å. A highly hydrated compound1a is less thermally stable compared to3a and4a . Whilst1a loses lattice water molecules above 74 °C, the two latter compounds start to dehydrate above 131 and 174 °C, respectively. Finally, PED analysis of computed normal vibrations conducted for optimized structures of Cu(H3 dmtZol)2 (H2 O), trans -Cu(H3 cbtZol)2 (H2 O)2 and trans -Cu(H3 cptZol)2 (H2 O)2 coordination units and related ligands1, 3 and4 has been used to assist in the detailed characterization of vibrational spectra of1a, 3a and4a .